2019
DOI: 10.1002/app.48661
|View full text |Cite
|
Sign up to set email alerts
|

The impact of polymer matrix blends on thermal and mechanical properties of boron nitride composites

Abstract: To improve mechanical and thermal properties of a hexagonal boron nitride platelet filled polymer composites, maleic anhydride was studied as a coupling agent and compatibilizer. Injection molded blends of acrylonitrile butadiene styrene (ABS), high-density polyethylene (HDPE), and maleic anhydride with boron nitride filler were tested for thermal conductivity and impact strength to determine whether adding maleic anhydride improved interfacial interactions between matrix and filler and between the polymers. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The two peaks of PW were ascribed to the melting of different molecular weight fraction of the wax that is, solid–solid transition and the melting of the crystallites respectively. Similar results were reported by as Molefi et al, [ 20 ] who studied the comparison of LDPE, LLDPE, and HDPE as matrices for phase change materials based on a soft Fischer‐Tropsch paraffin wax and Zhou et al, [ 30 ] who investigated the thermal properties of paraffin/HDPE phase change blends. Both authors observed that PW showed two endothermic peaks which were attributed to the melting of solid–solid phase transition and melting of crystallites, as explained earlier.…”
Section: Resultssupporting
confidence: 84%
“…The two peaks of PW were ascribed to the melting of different molecular weight fraction of the wax that is, solid–solid transition and the melting of the crystallites respectively. Similar results were reported by as Molefi et al, [ 20 ] who studied the comparison of LDPE, LLDPE, and HDPE as matrices for phase change materials based on a soft Fischer‐Tropsch paraffin wax and Zhou et al, [ 30 ] who investigated the thermal properties of paraffin/HDPE phase change blends. Both authors observed that PW showed two endothermic peaks which were attributed to the melting of solid–solid phase transition and melting of crystallites, as explained earlier.…”
Section: Resultssupporting
confidence: 84%
“…Composites filled with hBN can be processed by injection molding and extrusion, as opposed to the other two forms of BN, which have maximum hardness and are very abrasive materials. Numerous authors demonstrated thermally conductive composites filled with hBN on the basis of epoxy resins, 21,22 polyimide, 23 polyethylene, [24][25][26] polytetrafluoroethylene, 27 and so on. Unlike graphite, hBN is a good insulator of a non-black color, and is therefore more applicable as filler for heat-releasing materials that require a purely white appearance of final products, for example, heat sinks for LED lighting devices.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 11 prepared a polyetherimide (PEI)‐based composite that reinforced by multiwalled carbon nanotubes (MWCNTs) through in‐situ polymerization, from which the obtained tensile strength and modulus were increased by 22.6% and 39.5% in comparison with PEI, respectively. Thus, introducing appropriate fillers is widely proved as an effective strategy to improve the overall mechanical properties of polymers and to further endow composites with multitudinous functional properties 12–15 …”
Section: Introductionmentioning
confidence: 99%